2024
DOI: 10.1002/ntls.20230020
|View full text |Cite
|
Sign up to set email alerts
|

Commentary on the role of polyoxometalates in nature cybernetic loop

Kirill Yu. Monakhov

Abstract: The interplay between extraterrestrial, atmospheric, aqueous, interfacial, and hydrothermal processes is crucial for Earth's prebiotic chemistry. Volcanic terrains contain polyoxometalates (POMs). Some polyoxocuprates were identified as building blocks of fumarole minerals produced from high‐temperature gases. The existence of polyoxovanadate anions in acidified reducing volcanic aquifers cannot be excluded. At present, it can only be speculated whether life arose around natural POM deposits and/or around thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…The latter also occur in natural mineral phases. 22 Another type of oxovanadium compounds that may have potential applications in some form in computing are vanadyl porphyrins. 23 These vanadium( iv ) complexes (see, a crystal structure of a synthetic vanadyl petroporphyrin 24 ) were detected e.g.…”
Section: Vanadium Supplymentioning
confidence: 99%
“…The latter also occur in natural mineral phases. 22 Another type of oxovanadium compounds that may have potential applications in some form in computing are vanadyl porphyrins. 23 These vanadium( iv ) complexes (see, a crystal structure of a synthetic vanadyl petroporphyrin 24 ) were detected e.g.…”
Section: Vanadium Supplymentioning
confidence: 99%
“…Polyoxometalates (POMs) are a class of nanostructured transition metal oxide molecular clusters with a clear composition, diverse structures, adjustable structure volume, flexible scaffolds, easy derivatization, adjustable valence state, and reversible redox properties. Therefore, they are attractively researched in electrochemical energy storage, , catalytic, , medicine, , photo/electro-chromics, and nature . Different from the traditional transition metal oxides, POMs are able to store multiple electrons during the charging/discharging process, known as an “electron sponge”.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they are attractively researched in electrochemical energy storage, 14,15 catalytic, 16,17 medicine, 18,19 photo/electro-chromics, 20−22 and nature. 23 Different from the traditional transition metal oxides, POMs are able to store multiple electrons during the charging/ discharging process, known as an "electron sponge". A Keggintype polyoxometalate (PMo 12 ) was first reported to be used as the anode material of LIBs in 2012, and it was found that each PMo 12 molecule reversibly transfers 24 electrons during the lithiation and delithiation processes.…”
Section: ■ Introductionmentioning
confidence: 99%